Peranan Wanita Karier dalam Meningkatkan Pendapatan Ekonomi Keluarga di Kabupaten Kerinci - Syafrul Antoni; Ochi Aprila; Dafiar Syarif; Rezki Agrisa Ditama (LABATILA : Jurnal Ilmu Ekonomi Islam, 2022)
This study aims to determine the role of career women in improving the family economy in Kerinci Regency. This study used a qualitative approach, the authors used data analysis of the Miles and Huberman Models, namely data reduction, data display and conclusion/verification. In addition, the data was processed with the help of Nvivo software. 12 Plus. The results of the study concluded that career women have a relatively large role in increasing the family's economic income, with the additional income of these career women, all family expenses can be covered and all primary to tertiary needs can be met so that the family economy gradually increases. In addition, because of the economic improvement, many of the informants said they could even set aside a portion of their income to save and invest for the future. The impact of improving and increasing the family economy makes the family more harmonious and prosperous.